2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5614228
|View full text |Cite
|
Sign up to set email alerts
|

Infrared birefringence imaging of residual stress and bulk defects in multicrystalline silicon

Abstract: This manuscript concerns the application of infrared birefringence imaging ͑IBI͒ to quantify macroscopic and microscopic internal stresses in multicrystalline silicon ͑mc-Si͒ solar cell materials. We review progress to date, and advance four closely related topics. ͑1͒ We present a method to decouple macroscopic thermally-induced residual stresses and microscopic bulk defect related stresses. In contrast to previous reports, thermally-induced residual stresses in wafer-sized samples are generally found to be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Ganapati et al . and Sarau et al . suggested that dislocations are formed in mc‐Si in order to relieve thermally induced residual stresses during crystal growth, especially at triple points where the thermal stresses are known to be quite high.…”
Section: Resultsmentioning
confidence: 89%
“…Ganapati et al . and Sarau et al . suggested that dislocations are formed in mc‐Si in order to relieve thermally induced residual stresses during crystal growth, especially at triple points where the thermal stresses are known to be quite high.…”
Section: Resultsmentioning
confidence: 89%
“…Some crystal growth behaviors observed in melt growth processes were reviewed in this paper. Other significant issues not treated in this review include the dislocation/sub-grainboundary formation [82][83][84][85][86][87] and impurity behavior [88][89][90][91][92][93] in crystal growth processes. For the complete understanding of crystal growth mechanisms and the control of the macroand microstructures of mc-Si ingots, further data accumulation is required.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to mono‐Si, mc‐Si is cheaper and is widely used to produce low‐cost solar cells. However, mc‐Si wafering using DWS faces many challenges due to crystallographic defects such as grain/twin boundaries, dislocations, precipitates, and impurities . Dislocation density variation is correlated with variation in the fracture toughness, which affects the cutting characteristics .…”
Section: Introductionmentioning
confidence: 99%